Designing a novel Aerolysin-based multiepitope vaccine against Aeromonas hydrophila isolated from Osphronemus goramy using reverse vaccinology: an in silico approach - Rozi, .; Tyasningsih, Wiwiek; Rahmahani, Jola; Aksono, Eduardus Bimo; Yunus, Muchammad; Al Arif, Mohammad Anam; Kuncorojati, Suryo; Kusdarwati, Rahayu; Sari, Putri Desi Wulan; Azmai, Mohammad Noor Amal; Salleh, Annas; Khanand, Nadeem; et al. (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Aeromonas hydrophila, a gram-negative bacterium, is a major pathogen responsible for various diseases in mammals, reptiles, amphibians, fish, and humans. Targeting the specific toxin aerolysin in A. hydrophila is crucial to address antibiotic resistance and the lack of adequate and protective vaccines against this intracellular and extracellular pathogen. This study aimed to identify a multi-epitope vaccine (MEV) candidate targeting the aerolysin toxin to combat the disease effectively. Standard biochemical characterization methods, detection of PCR, and sequencing of the 16S rRNA, rpoB, and aerA genes identified the isolate AHSA1 as A. hydrophila isolated from O. goramy. Subsequently, we identified B and T cell epitopes on the aerolysin protein and predicted MHC-I and MHC-II epitopes. The epitopes were then evaluated for toxicity, antigenicity, allergenicity, and solubility. The vaccine design integrated multi-epitope constructs, utilizing specialized linkers (GPGPG and EAAAK) to connect epitope peptides with the cholera toxin B subunit as an adjuvant, thereby enhancing immunogenicity. Ramachandran plots showed that 85.25% of the residues were in the most favorable regions, followed by additionally allowed regions (10.80%), generously allowed regions (1.30%), and disallowed regions (2.65%), confirming the feasibility of the modeled vaccine design. Based on docking simulations, the MEV had strong binding energies with TLR-4 (-1081.4 kcal/mol), TLR-9 (-723.2 kcal/mol), MHC-I (-866.2 kcal/ mol), and MHC-II (-9043.3 kcal/mol). Based on computational modeling, we expect the aerolysin MEV candidate to activate diverse immune mechanisms, stimulate robust responses against A. hydrophila, and maintain safety. The significant solubility, absence of toxicity and allergic response contribute to the potential clinical utility of this vaccine candidate.